Automated prismatic battery recycling using a 6-DoF robotic arm: co-simulation and validation via Matlab/CoppeliaSim - Fang, Caixi (Nanyang Technological University, 2025)
The accelerated adoption of electric vehicles (EVs) has resulted in a significant increase in the number of end-of-life (EoL) electric vehicle batteries (EVBs), posing significant environmental and economic challenges. Traditional manual recycling processes for EVBs are labor-intensive, costly, and hazardous due to toxic battery components. This study proposes an automated robotic solution to streamline EVB recycling, focusing on prismatic battery cells, which dominate the European market. A 6-degree-of-freedom (6-DoF) robotic arm was designed using SolidWorks, with inverse kinematics and trajectory planning algorithms implemented in MATLAB. A co-simulation framework integrating MATLAB and CoppeliaSim validated the robotic arm’s ability to autonomously grasp, transport, and place prismatic batteries with millimeter-level precision. Key results include smooth joint motion profiles (velocity errors ¡ 5%), successful handling of vari- able battery sizes (0.17–0.42 m), and a 92% grasping success rate across 50 test cycles. The system reduces reliance on manual labor by 60% in simulated disassembly tasks, demonstrating its potential to enhance operational efficiency and safety in battery recycling plants. This work advances robotic automation in sustainable manufacturing, offering a scalable solution for industrial EVB re- cycling.